A retrospective analysis omalizumab treatment patterns in patients with chronic spontaneous urticaria: a real‐world study in Belgium. (19th August 2019) - Lapeere, H.; Baeck, M.; Stockman, A.; Sabato, V.; Grosber, M.; Moutschen, M.; Lambert, J.; Vandebuerie, L.; de Montjoye, L.; Rabijns, H.; Allewaert, K.; Schrijvers, R.
Abstract: Background: Chronic spontaneous urticaria (CSU) is characterized by the repeated occurrence of persistent hives and/or angioedema for ≥6 weeks, without specific external stimuli. H1 ‐antihistamines have long been the standard of care of CSU, but many patients remain uncontrolled even at 4× the approved dose. Add‐on therapy with omalizumab has proven effective in clinical trials, but little is known about omalizumab treatment in Belgium. Objective: To collect real‐world clinical data on omalizumab treatment in adults with CSU in Belgium. Methods: This was an observational, retrospective chart review of adults with CSU, who initiated omalizumab treatment between August 2014 and December 2016 (maximum 28 months follow‐up). Results: In total, 235 patients were included (median time from symptom onset to diagnosis, 5.4 months; median time from diagnosis to commencing omalizumab, 6.7 months). Treatments used before/after commencing omalizumab did not always adhere to guidelines; many patients (26.4%/11.1%) received first‐generation H1 ‐antihistamines, while 20.4% used omalizumab monotherapy after initiating treatment. The mean interval between omalizumab administrations was 4.8 (SD 1.7) weeks; 67.8% of patients had ≥1 interval prolongation and/or shortening. Mean baseline 7‐day Urticaria Activity Score (UAS7) was 32.0 (SD 6.05); this improved to 12.6 (SD 11.2) after 1 month of omalizumab. About 67.2% of patients reached UAS7 ≤ 6 (well controlled) during the study. A total of 87 patients stopped omalizumab and never restarted before the end of the observation period; the most prevalent reason was remission of symptoms (49.4% of patients), followed by lack of effect (12.6%), lost to follow‐up (6.9%) and adverse events (3.4%). Headache was the most common adverse event ( n = 8/82). No anaphylaxis was reported. Conclusions: This study revealed that patients initiated on omalizumab in Belgium had severe CSU at baseline, and showed substantial improvements after 1 month of treatment. Greater adherence to the prescription of guideline‐recommended medications is needed for the treatment of CSU.